Surface Subsidence Caused By Flooding and Dewatering at Four Abandoned Coalmines in the US - Kewal K. Kohli; Stefanie Self (International Conference on Ground Control in Mining, 2010)
"Three cases of surface subsidence investigated over abandoned coal mines after flooding in one case and dcwatering in two cases are presented in this paper. Mining was conducted by the room and- pillar method at all the mines leaving stable pillars. This paper will discuss the background chain of events and the likely causes of the pillar failure resulting in surface subsidence.CASE NO.1BackgroundThe Pittsburgh scam was mined in 1960 by the room-and- pillar method, leaving pillars (Figure I) through Mine A. located in Monongalia County. West Virginia.The mining height in U1is area was 1.83 m (6 ft) with an average mining depth of 140 m (460 ft). The mining recovery was 62% and the safety factor of the pillars was calculated at 1.15 using the Bieniawski ( 1984) fom1ula. For stable pillar design. a 1.5 safety factor is recommended. A 1.15 safety factor is considered marginal. Pumping continued after the mine was shut down in 1960 to prevent water seeping into an adjoining mine owned by the same company. The pumping ceased on December 12. 2003, and the mine was allowed to flood. The water level rose about 17 m (55 ft) by August 3 1, 2004, based on observations in a nearby borehole. On September 3, 2004 surface subsidence occurred above this area causing damage 10 a residence (Figure 2).Summary of InvestigationThe floor of the Pittsburgh coal scam played a strong role in the pillar failure. In this area, the immediate floor of the Pittsburgh seam consists of about two feet of fireclay. Extensive damage to the surface house was an indication that a major collapse below the surface had occurred. The pillars supporting the overlying strata were evaluated to find the cause of their failure. The pillars in the Pittsburgh seam (sec Figure I) had a marginal safety factor of 1.15 before flooding and were stable for 26 years. Once the mine was flooded the water level in the Pittsburgh seam rose by 17 m (55 ft). Shortly thereafter the fireclay in the floor weakened, resulting in several pillars punching into the floor unevenly making the immediate roof unstable. The overburden strata supported by these pillars also subsided do"" n into the mine, causing damage to several house on the surface."